2018
DOI: 10.1101/258632
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AAK1 inhibits WNT signaling by promoting clathrin-mediated endocytosis of LRP6

Abstract: 40 SUMMARY STATEMENT 41A gain-of-function screen of the human kinome revealed AAK1 as a negative regulator of WNT 42 signaling. We show that AAK1 promotes clathrin-mediated endocytosis of LRP6, resulting in 43 downregulation of WNT signaling. We use a new selective and potent AAK1/BMP2K small 44 molecule probe to validate our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The binding of NECAP recruits SNX9 for the late stages of CCP formation. In another study, 106 AAK1 phosphorylates the μ2 subunit of AP2 to promote CME of LRP6 in WNT signaling (Figure 10D).…”
Section: Intracellular Ensmentioning
confidence: 90%
“…The binding of NECAP recruits SNX9 for the late stages of CCP formation. In another study, 106 AAK1 phosphorylates the μ2 subunit of AP2 to promote CME of LRP6 in WNT signaling (Figure 10D).…”
Section: Intracellular Ensmentioning
confidence: 90%
“…165 Therefore, it can be concluded that clathrin clears the LRP6 receptor from the plasma membrane. 166 6.3. Notch Signaling Pathway.…”
Section: Wnt Signaling Pathwaymentioning
confidence: 99%
“…68 Further studies focused on the development of selective NAK inhibitors are needed to improve the knowledge around the NAK family members and to confirm their potential as broad-spectrum antivirals. In this regard, the use of chemical probes such SGC-GAK1 69 (32, Figure 5) or SGC-AAK-1 70,71 (33, Figure 5) will be of utmost importance. It is also noteworthy that the structurally related negative controls, 34 and 35, are available (Figure 5).…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%